Simultaneous quantitative analysis of Ni, VO, Cu, Zn and Mn geoporphyrins by liquid chromatography-high resolution multistage mass spectrometry: Method development and validation - Woltering, M.; Tulipani, Svenja; Boreham, C.; Walshe, J.; Schwark, Lorenz; Grice, Kliti (Elsevier Science BV, 2016)
© 2016 Elsevier B.V. A method is described for the identification and quantification of Cu, Ni, VO, Zn and Mn metalloporphyrins in geological samples using a high performance liquid chromatography (HPLC) system coupled to a high resolution Thermo Orbitrap XL mass spectrometer (MS). The linear correlation of the detector response to the compound concentrations in Cu, Ni, VO, Zn and Mn porphyrin standards (R2 values between 0.9975 and 0.9994), verified the suitability of the methodology for the quantification of these compounds. Furthermore, the method was validated by the analysis of complex porphyrin distributions in geological sample isolates from the Australian Toolebuc Formation and Bight Basin. By using the high resolution of the Orbitrap MS detector it was not only possible to reproduce the porphyrin distributions reported from previous analyses of the same isolates, but also to identify and resolve a range of additional compounds such as an iso-butyl C34 VO porphyrin indicative of palaeoenvironmental photic zone euxinia and several Cu and Zn porphyrins. The methodology described here provides a new high resolution tool for routine analysis of complex metalloporphyrin distributions in geological sample extracts, enabling the simultaneous quantitative analysis of Cu, Ni, VO, Zn and Mn porphyrins without the need of prior de-metalation or further fractionation of the porphyrin extract. The high resolution of the Orbitrap MS combined with the ability to perform multistage mass spectrometry leads to a significant improvement in compound detection and identification, which shows a high potential in the analysis of low abundance porphyrins, such as high-molecular-weight porphyrins with extended alkyl side-chains.